2007
DOI: 10.1186/1477-9560-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel in Orthopaedic patients: a review of current practice in Scotland

Abstract: Background: Clopidogrel bisulfate is an antiplatelet agent used to prevent ischaemic events in patients with vascular disease. Current guidelines recommend withholding clopidogrel for 7 days pre-operatively. However these are not based on orthopaedic patients. We therefore decided to survey current orthopaedic practice to see whether this complied with available clinical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
(7 reference statements)
0
22
0
Order By: Relevance
“…[15][16][17][18] Delay in surgery more than 4 days in patients who had surgical treatment of a hip fracture has been shown to significantly increase mortality at 30 days. 19 A recent report showed patients who had surgery less than 36 hours after injury had a reduced risk for pressure ulcers, improved ability for independent living, and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Delay in surgery more than 4 days in patients who had surgical treatment of a hip fracture has been shown to significantly increase mortality at 30 days. 19 A recent report showed patients who had surgery less than 36 hours after injury had a reduced risk for pressure ulcers, improved ability for independent living, and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel belongs to the class of anti-platelet agents and is indicated for prevention of arterial thromboembolism in patients with peripheral arterial diseases or patients with acute coronary syndrome (ACS) who are treated medically or through coronary revascularization procedures 1,2 . With global sales of $9.1 billion (US dollars) in 2009, clopidogrel is the second best selling drug worldwide 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent audit among vascular surgeons in the United Kingdom showed wide variation in practice with no consensus with regard to thienopyridine use and major vascular surgical procedures. 15 Similarly, Joseph et al 16 showed a lackofconsensuswithregardtostoppingclopidogrel use in the perioperative period among orthopedic surgeons.…”
Section: Discussionmentioning
confidence: 99%